Acrogenospora tongrenensis sp. nov. (Minutisphaerales, Dothideomycetes), a freshwater hyphomycete from Guizhou, China - Li, Wen-Mei; Zhang, Qin-Fang; Liu, Li-Li; Luo, Xing-Yu; Habib, Kamran; Shen, Xiang-Chun; Chen, Yang; Li, Qi-Rui (Phytotaxa, 2026)
During a study on the diversity and taxonomy of hyphomycetous freshwater fungi in Guizhou, China, two strains of Acrogenospora were isolated from decaying wood. Morphological and multilocus phylogenetic analyses of ITS, LSU, SSU, rpb2 and tef1-α sequence data revealed that the two strains represent an undescribed taxon, which we here described and illustrated under the name Acrogenospora tongrenensis sp. nov. According to the phylogenetic analysis the new species is closely related to A. stellata, but can be distinguished by its longer conidiophores (300–700 × 5–8 µm vs. 200–570 × 6–10 µm) and larger, acropleurogenous conidia (34–44 × 25–37 µm vs. acrogenous 25–30 × 15–20 µm). A detailed description, illustrations, and a phylogenetic tree are provided to support the recognition and accurate identification of this new species.